The Implementation of CHSE Program at Sibayak Berastagi Hotel to Increase Guest Trust - Liyushiana; Chafizah; Citra Sinuraya; Esra Sibarani; Roel Dizastra (Journal Hotspot, 2024)
CHSE certification is one of the strategic policies set nationally by the Ministry of Tourism and Creative Economy. One of the hotels that has been certified CHSE is Hotel Sibayak Berastagi. The various dynamics after this hotel has obtained CHSE certification need to be considered, for example how the hotel adopts the latest rules in accordance with CHSE policies. The big question is how the hotel will go further in implementing CHSE regarding the existing environmental conditions around it. So the purpose of this study is to analyze the steps for implementing CHSE including seeing how the adoption of related policies and environmental conditions; as well as to analyze the challenges and solutions made by the hotel in implementing CHSE. The method used is qualitative with an interactive approach, where data collection is carried out by observation and interviews with hotel management. The results showed that Hotel Sibayak Berastagi has consistently implemented CHSE and is adaptive to new rules in the application of health protocols. Even in terms of security, Hotel Sibayak Berastagi is also active in informing about the status of the Sinabung volcano through its website. Some of the challenges faced are ensuring employee discipline in the use of PPE and awareness of guests to use masks at this time. Various alternative solutions are offered, starting from improving the mechanism, providing quality PPE for employees to offering free masks for guests of the Sibayak Berastagi Hotel so that they are disciplined in maintaining health protocols.